2014
DOI: 10.1186/1472-6955-13-27
|View full text |Cite
|
Sign up to set email alerts
|

Organization of nursing care in three Nordic countries: relationships between nurses’ workload, level of involvement in direct patient care, job satisfaction, and intention to leave

Abstract: BackgroundHealth care systems in Finland, Norway and Sweden share many similarities, e.g. full-coverage and tax-financed, with predominately public sector hospitals. Despite similarities, there are differences in the working situations for RNs within these Nordic countries. The aim of this study was to analyze associations between RNs’ patient workload and level of involvement in direct patient care, their job satisfaction and intention to leave in these countries.MethodsA workforce survey was conducted throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 17 publications
7
30
0
1
Order By: Relevance
“…More specifically, negative correlations were detected not only with the overall IWS score, but also with Status, Interaction, Tasks and Autonomy sub-scores. Although literature reports on workload and nurse job satisfaction are limited, our results are in accordance with the study that demonstrated a correlation between high workload and poor job satisfaction, followed by an intention to quit, among registered nurses in Nordic hospitals (28) . It appears that the current worldwide nursing shortage contributes to heavier workload, which leads to a more stressful job environment with more tasks to accomplish (under time pressure) and conflicts among healthcare professionals.…”
Section: Discussionsupporting
confidence: 81%
“…More specifically, negative correlations were detected not only with the overall IWS score, but also with Status, Interaction, Tasks and Autonomy sub-scores. Although literature reports on workload and nurse job satisfaction are limited, our results are in accordance with the study that demonstrated a correlation between high workload and poor job satisfaction, followed by an intention to quit, among registered nurses in Nordic hospitals (28) . It appears that the current worldwide nursing shortage contributes to heavier workload, which leads to a more stressful job environment with more tasks to accomplish (under time pressure) and conflicts among healthcare professionals.…”
Section: Discussionsupporting
confidence: 81%
“…Currently, Sweden has no formalized system on a national or county level for clinical career ladders among nurses, neither for wages nor for further education, although certain employers might have their own standards (Lindqvist et al . ). The present study provided a deeper understanding of how Herzberg's theory can explain what motivates registered and assistant nurses to work in mental health care.…”
Section: Discussionmentioning
confidence: 97%
“…This has been suggested in several studies, and Lindqvist et al . () found that significantly more registered nurses from Norway reported that they would recommend their hospital to a colleague as a good place to work compared to Swedish nurses.…”
Section: Introductionmentioning
confidence: 99%
“…A study of nursing staff in Finland, Norway and Sweden found that most participants were satisfied with their profession, but workers with higher workload had lower professional fulfillment and the intention to leave their job (26) .…”
Section: Discussionmentioning
confidence: 99%